IMPLIKASI PERTARUNGAN IDEOLOGI TERHADAP PENDIDIKAN DI INDONESIA - Afriantoni Afriantoni (Ta'dib: Jurnal Pendidikan Islam, 2011)
The battles of ideology after Indonesia’s independence has implied indirectly toward the development of national education which was established by the Indonesian nation. Battles and debates of the concept of Indonesian education system has been becoming public consumptions that never ends. The implication is the double educational system which happens in Indonesia nowadays, and those are the real forms of ideology battles. Consequently the battles linearly impact on the institution dichotomy, educational objective, scientific and curriculum in every Indonesian  educational unit.